Pengaruh Upah dan Insentif terhadap Produktivitas Kerja Karyawan di Medan - Amanda, Melinda; Hermana, Cecep (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study, conducted thoroughly, aims to investigate the connection between employee productivity in Medan and wages and incentives. The qualitative descriptive research investigation employs a comprehensive range of library resources to examine and interpret prior research on the effects of salaries and incentives on worker productivity in many Medan-based businesses. The data, meticulously gathered from a wide array of existing scientific research journals found in the literature, was analyzed and assessed. The findings, which are robust and reliable, indicate a strong relationship between employee wages and job productivity, with the amount of compensation and incentives that the firm offers influencing this relationship. It is important to note that in addition to wages and incentives, there are a number of other variables that might affect how productive employees work